The relationship of some teaching competencies of a professor of physical education and sports with personality traits in the secondary phase - CHAREF , ISMAIL; GUENDOZENE , NADHIR (Social Empowerment Journal, 2021)
This study aimed to highlight the relationship of some teaching competencies of a professor of physical education and sports with personality traits in the secondary education stage, and to reveal the effect of these characteristics on the professional performance of the professor, whether in a positive or negative direction. In this study, the researcher relied on a sample of 32 physical education and sports professors in the secondary phase of the municipality of Laghouat, distributed into 13 secondary schools, and the researcher used the relational descriptive approach, The study tool was represented in the personality traits scale and a questionnaire that represents some teaching competencies, and the researcher concluded that the positive personality traits of the professor (the trait of bearing responsibility, the trait of self-confidence, the trait of emotional balance) have a positive effect on the teaching competencies of the professor during the class, while the trait of introversion It has a negative impact on the professional performance in general